Endophyte-mediated chromium detoxification in Sorghum sudanense: plant growth promotion and soil microbial enrichment - Yang, Wenling; Quan, Shujing; Lei, Gao; Liu, Ling; Zhang, Yongzhan; Zhen, Jing; Mu, Qi; Xu, Hongguang; Ran, Huomiao; Li, Liangliang (Frontiers in Microbiology, 2026)
Phytoremediation, assisted by endophytes, showed great promise for the efficient remediation of chromium (Cr)-contaminated soil. Three endophytic bacterial strains (SE16, SE19, and SE47) were isolated from various tissues of Sorghum sudanense. The pot experiment was designed to evaluate the potential of these endophytes, applied individually or in combination, to enhance the phytoremediation efficiency of S. sudanense in Cr-contaminated soil. The results demonstrated that inoculation with endophytes increased plant height and root length by 26.4–49.2% and by 63.5–122.8%, respectively. With the exception of the SE47 treatment, the fresh weights of the shoot increased significantly, reaching 2.01–3.08 times that of the non-inoculated control. Endophyte inoculation also led to a marked reduction in the Cr content in the shoots and roots of S. sudanense. The chlorophyll content increased, while the malonaldehyde (MDA) content decreased significantly after inoculation, indicating the alleviation of the cytotoxicity of Cr. The peroxidase (POD) activity in both the shoots and roots of S. sudanense decreased after inoculation. In shoots, catalase (CAT) activity was significantly lower in the combined inoculation treatments than in the non-inoculated control. In contrast, single inoculation treatments significantly increased CAT activity in roots compared to the control. Furthermore, endophyte inoculation increased soil organic matter (OM) and alkaline phosphatase activity. At the genus level, endophyte inoculation increased the relative abundance of Delftia and Saccharimonadales, which may contribute to reducing the toxic effects of heavy metals to plants. Our findings indicated that the endophytic bacteria are promising candidates for promoting plant growth and facilitating microbe-assisted phytoremediation in heavy metal-contaminated soil.